The FGF21 response to fructose predicts metabolic health and persists after bariatric surgery in obese humans - Kasper W. ter Horst; Pim W. Gilijamse; Ahmet Demirkiran; Bart A. van Wagensveld; Mariette T. Ackermans; Joanne Verheij; Johannes A. Romijn; Max Nieuwdorp; Eleftheria Maratos-Flier; Mark A. Herman; Mireille J. Serlie (Elsevier, 2017)
Objective: Fructose consumption has been implicated in the development of obesity and insulin resistance. Emerging evidence shows that fibroblast growth factor 21 (FGF21) has beneficial effects on glucose, lipid, and energy metabolism and may also mediate an adaptive response to fructose ingestion. Fructose acutely stimulates circulating FGF21 consistent with a hormonal response. We aimed to evaluate whether fructose-induced FGF21 secretion is linked to metabolic outcomes in obese humans before and after bariatric surgery-induced weight loss. Methods: We recruited 40 Roux-en-Y gastric bypass patients and assessed the serum FGF21 response to fructose (75-g fructose tolerance test) and basal and insulin-mediated glucose and lipid fluxes during a 2-step hyperinsulinemic-euglycemic clamp with infusion of [6,6-2H2] glucose and [1,1,2,3,3-2H5] glycerol. Liver biopsies were obtained during bariatric surgery. Nineteen subjects underwent the same assessments at 1-year follow-up. Results: Serum FGF21 increased 3-fold at 120 min after fructose ingestion and returned to basal levels at 300 min. Neither basal FGF21 nor the fructose-FGF21 response correlated with liver fat content or liver histopathology, but increased levels were associated with elevated endogenous glucose production, increased lipolysis, and peripheral/muscle insulin resistance. At 1-year follow-up, subjects had lost 28 ± 6% of body weight and improved in all metabolic outcomes, but fructose-stimulated FGF21 dynamics did not markedly differ from the pre-surgical state. The association between increased basal and stimulated FGF21 levels with poor metabolic health was no longer present after weight loss. Conclusions: Fructose ingestion in obese humans stimulates FGF21 secretion, and this response is related to systemic metabolism. Further studies are needed to establish if FGF21 signaling is (patho)physiologically involved in fructose metabolism and metabolic health.